1991
DOI: 10.1073/pnas.88.6.2312
|View full text |Cite
|
Sign up to set email alerts
|

Curved DNA without A-A: experimental estimation of all 16 DNA wedge angles.

Abstract: The principal sequence feature responsible for intrinsic DNA curvature is generally assumed to be runs of adenines. However, according to the wedge model of DNA curvature, each dinucleotide step is associated with a characteristic deflection of the local helix axis. Thus, an important test of a more general view of sequence-dependent DNA curvature is whether sequence elements other than A-A cause the DNA axis to deflect. To address this question, we have applied the wedge model to a large body of experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
379
3
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(396 citation statements)
references
References 42 publications
12
379
3
1
Order By: Relevance
“…For example, a large upfield shift of H2' in a cis-platinated duplex was attributed to shielding by the destacked adenine base of the kinked structure [46]. It is now well established that Y-R steps (Y= pyrimidine, R= purine) like CpG are geometrically flexible [47] and several studies have shown that CpG steps are involved in DNA bending [48,49]. Since linear dichroism shows that very low loading of [Fe 2 L 3 ] 4+ have a dramatic bending effect on the DNA [1] and atomic force microscopy images show that this is an intramolecular effect resulting in coils of DNA [1] it is interesting to look for similar bending pattern in the NMR data.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a large upfield shift of H2' in a cis-platinated duplex was attributed to shielding by the destacked adenine base of the kinked structure [46]. It is now well established that Y-R steps (Y= pyrimidine, R= purine) like CpG are geometrically flexible [47] and several studies have shown that CpG steps are involved in DNA bending [48,49]. Since linear dichroism shows that very low loading of [Fe 2 L 3 ] 4+ have a dramatic bending effect on the DNA [1] and atomic force microscopy images show that this is an intramolecular effect resulting in coils of DNA [1] it is interesting to look for similar bending pattern in the NMR data.…”
Section: Methodsmentioning
confidence: 99%
“…The dinucleotide composition is known to account for the curvature (18) and therefore the supercoiling of double-stranded DNA. For examination of this physicochemical aspect of DNA regarding thermostability, the following index has been introduced:…”
Section: Discussionmentioning
confidence: 99%
“…(AT)n and poly(dA)). An example is the central 'aaaaatatata' motif in synl (Table 2 [6,22]). Comparing the extreme values in Tables 2 and 3 one can see that the high helical asymmetry values characteristic of strong intrinsic curvature are conspicuously missing from the genomes analyzed so far.…”
Section: Asymmetric Bendability Reflects Propensity To Curvaturementioning
confidence: 99%